DETERMINATION OF PIPERINE ISOLATE FROM JAVA CHILLI (Piper Retroofactum Vahl.) Using the High Performance Liquid Chromatography (HPLC) method - Christina, Odilia Dea; Mahesa, Sandi; Elsa, Limpat (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2023)
Java chili fruit (Piper Retroofactum Vahl.) can be used in concoctions to treat fever, flatulence, heartburn, vomiting, overcome digestive disorders, stimulate appetite. In the traditional medicine industry in Indonesia, Java chili is one of the most needed raw materials, 9.5% of the total simplicia. Javanese chilies are round and dark green to brown in color. The content of the main secondary metabolites in chili plants is piperine, pipernaline, guineensine and essential oils. The purpose of this study was to determine the piperine content isolated from Java chili using the HPLC method. The column used is a C-18 type column, 2489 UV/Visible detector light. The mobile phase used was Acetonitrile : Methanol : Aquabidest (65:5:30) v/v. The isolation results obtained yield of 0.20% piperine isolate has a spicy taste, needle-shaped blackish brown color, difficult to dissolve in water and easily soluble in ethanol.From the results of the assay, the piperine content data was obtained at 37.48%